Contention works efficacy study of coastal erosion in Conceição da Barra – ES - Ayala Espinoza, Juan Alfredo (Guará Journal, 2017)
Studies conducted in the city of Conceição da Barra during the period of 07/26/2013 to 06/06/2014 proved that its beaches can be classified as reflective to intermediate of high energy. Compara tive analysis of the coastline and the mouth of the São Mateus river through satellite images from 1985 to 2013 showed erosion, especially at the Bugia’s beach sector. Sedimentary analysis showed the reworking of postbeach sediments towards the shoreface sector. By the profiles held in the containment works is observed variability of near beach morphology, the one that shows negative sediment balance in the north of the study area and positive near the mouth of the São Mateus river. A possible explanation for the negative sediment balance in the north of the study area are the man induced changes in the mouth of the Itaúnas river, reducing the sediment influx transported by coastline drift to the sector of Guaxindiba’s beach. In conclusion, it is necessary to review the design and executive project of containment works in order to correct any errors, once engineering works are partially meeting the purpose that they were designed for.